"We want our freedom back, that's our only need": a qualitative study of health and social needs among asylum seekers and undocumented migrants crossing the borders from Belarus to Lithuania - Rabie Adel El Arab; Rabie Adel El Arab; Rabie Adel El Arab; Rabie Adel El Arab; Rita Urbanavice; Rita Urbanavice; Agne Jakavonyte-Akstiniene; Agne Jakavonyte-Akstiniene; Marija Skvarcevskaja; Marija Skvarcevskaja; Donatas Austys; Erica Briones-Vozmediano; et al. (Frontiers Media S.A., 2024)
BackgroundThe influx of undocumented migrants and asylum seekers into Lithuania, particularly during the COVID-19 pandemic, presents unique public health challenges. This study employs the Social Determinants of Health framework to explore the healthcare and social needs of this vulnerable population.MethodsIn May 2022, we carried out a qualitative study through semi-structured interviews with asylum seekers across four centers in Lithuania. Employing both purposive and snowball sampling techniques, we selected participants for our investigation. The study comprised 21 interviews-19 conducted in Arabic and 2 in English-with durations ranging between 20 and 40 min each. We audio-recorded all interviews, transcribed them verbatim, and subsequently performed a thematic analysis using Atlas.ti software. This process of design and analysis strictly followed the principles of thematic analysis as outlined by Braun and Clarke, guaranteeing methodological precision and rigor.Findings21 interviews revealed critical insights into the healthcare access challenges, mental health issues, and social integration barriers faced by the participants. Key themes included 'Healthcare Needs and the Impact of the COVID-19 Pandemic 'and 'Social needs and Aspirations Amidst Pandemic-Induced Uncertainty '. The findings highlight the multifaceted healthcare and social needs of asylum seekers, juxtaposed against significant barriers they face. Access to medical services is hindered by long waiting times and financial constraints, especially for specialized care such as dental services. Communication issues during medical appointments due to language barriers and the lack of gender-specific healthcare, such as access to gynecological services, further exacerbate the challenges. Additionally, the COVID-19 pandemic introduces hurdles such as limited testing, isolation measures, language-specific information barriers, and insufficient social distancing practices. Mental health has emerged as a critical concern, with asylum seekers reporting significant stress and emotional exhaustion due to uncertainty and restrictive living conditions. Social needs extend to delayed asylum application processes, inconsistent language education opportunities, inadequate clothing, and nutrition that lacks cultural sensitivity, and living conditions characterized by overcrowding and insufficient facilities. The restricted freedom of movement within asylum seeking centres severely impacts their psychological well-being, underscoring a deep longing for autonomy and a better life despite the myriad of challenges faced.DiscussionThe study illustrates the complex interplay between migration, health, and social factors in the context of a global pandemic. It highlights the need for culturally sensitive healthcare services, mental health support, and structured language education programs. Offering educational avenues alongside language courses for children and adults is essential for fostering social inclusion and securing economic prosperity. Addressing the challenge of language barriers is of utmost importance, as these barriers significantly impede undocumented migrants' and asylum seekers employment opportunities and their access to crucial services. The findings emphasized immigration as a health determinant and underscored the importance of inclusive health policies and advocacy for undocumented migrants and asylum seekers' rights and needs.ConclusionThere is an urgent need for comprehensive policies and practices that are grounded in the principles of equity, compassion, and human rights. Additionally, advocating for practice adaptations that are culturally sensitive, linguistically inclusive, and responsive to the unique challenges faced by undocumented migrants and asylum seekers. As global migration continues to rise, these findings are crucial for informing public health strategies and social services that cater to the diverse needs of this vulnerable population.